Mechanistic Evidence in Support of Alpha1-Antitrypsin as a Therapeutic Approach for Type 1 Diabetes. (November 2014) - Fleixo-Lima, Gabriella; Ventura, Hilla; Medini, Michal; Bar, Liliana; Strauss, Pnina; Lewis, Eli C.
Utilizing endogenous molecules as a therapeutic approach is almost unequivocally superior to engineered or synthetic molecules. However, one rarely encounters an anti-inflammatory, cytoprotective, immunomodulatory and wound-healing molecule that has been available for use for decades. α1-antitrypsin (AAT), a circulating protein that rises more than 4-fold during acute-phase responses, has been administered for a rare genetic deficiency at large doses, for life. Aside from advances in insulin therapy, medical research in type 1 diabetes (T1D) has predominantly focused on autoimmunity—controlling the adaptive immune response. However, it is now appreciated that one may need to extend therapeutic targets to incorporate immune responses to cellular injury, as well as promote selective control over excessive inflammation and early tissue repair . Recent data suggest that tissue damage related to lung and renal ischemia-reperfusion injury, stroke, and ischemic heart disease is markedly reduced by AAT. AAT was also shown to protect pancreatic islet β cells at multiple levels. Unlike classic immunosuppressive and anti-inflammatory approaches, AAT exerts some antiviral and antibacterial activities. Based on these and other reports, AAT is under evaluation for treatment of T1D patients in multiple clinical trials. Initial results suggest that AAT therapy could potentially improve insulin production without adverse effects. Up to 50% of individuals displayed improved islet function. It is a rare occurrence in T1D research that a therapy is offered that holds a safety profile equal or superior to that of insulin alone. While placebo-controlled trials are ongoing, the mechanism(s) behind these favorable activities of AAT are still being explored.